Minat Perilaku Pengguna Mobile Banking pada Perguruan Tinggi Agama Islam - Anjani, Nia; Kalsum, Ummi; Alwahidin (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2024)
This study aims to examine the effects of perceived ease of use, perceived usefulness, attitude towards behavior, subjective norms, and behavioral control—on students' behavioral intention to use mobile banking. A quantitative research approach was employed to validate the data collected. This research was conducted in one of Islamic Higher Education in Indonesia, namely IAIN Kendari. The sample consisted of 100 students from IAIN Kendari who actively use mobile banking, selected using a purposive sampling technique. Data was gathered through questionnaires and the analysis was conducted using path analysis regression. The results indicate that students' behavioral intention to use mobile banking is positively influenced by their perceptions of ease of use, usefulness, attitude towards the behavior, subjective norms, and behavioral control. The more favorable individuals' perceptions of convenience, utility, and control over mobile banking usage, the stronger their intention to use the technology. These factors interact with each other, shaping users' behavioral intention to adopt mobile banking.